The Early Umayyad Period: Formation, Political Development, Social Conditions, Religious Affairs, and Civilizational Progress - Ikhsan Darmawan; Siska Afriany; Syarifah (Jurnal Pendidikan Islam, 2024)
The background of this research is to understand the significant role of the Umayyad Caliphate in the political and social development of Islamic civilization, which initially faced challenges due to the conflict and machinations perpetrated by Muawiyah against Caliph Ali bin Abi Talib, as well as the transition of the caliphal selection system from democratic to monarchical. The objective of this study is to analyze the contributions of this dynasty to the formation of advanced political and social institutions. This research adopts a qualitative approach with a historical perspective. Data collection techniques involve a literature review encompassing primary and secondary sources related to the history of the Umayyad Caliphate. Data analysis is conducted using descriptive-analytical methods to depict and evaluate the political and social developments during the reign of this dynasty. The findings indicate that the Umayyad Caliphate successfully brought significant progress in the political realm, such as the establishment of governmental laws, ministerial councils, state secretariat institutions, and specialized political advisors, which contributed to the complexity of governance and state administration during its time.